Предмет: Математика, автор: dezant

2(x+3)^2-2(3x-1)^2=5x(2x-3)-10

Ответы

Автор ответа: Apofeoz
0

2(x+3)^2-2(3x-1)^2=5x(2x-3)-10,\2(x^2+6x+9)-2(9x^2-6x+1)=10x^2-15x-10,\2x^2+12x+18-18x^2+12x-2-10x^2+15x+10=0,\-26x^2+39x+26=0,\26x^2-39x-26=0,\D=39^2-4*26*(-26)=4225,\x_1=frac{39+sqrt{4225}}{2*26}=frac{39+65}{52}=frac{104}{52}=2;\x_2=frac{39-65}{52}=frac{-26}{52}=-frac{1}{2}=-0,5.

Ответ: x_1=2, x_2=-0,5.

Автор ответа: Аэроплан
0

Решение:

2(x+3)²-2(3x-1)²=5x(2x-3)-10

2(х²+6х+9)-2(9х²-6х+1)=10х²-15х-10

2х²+12х+18-18х²+12х-2-10х²+15х+10=0

-26х²+39х+26=0

26х²-39х-26=0

D=1521+2704=65²

x₁=(39-65)/52=-26/52=-0,5

x₂=(39+65)/52=2

Ответ:x₁=-0,5;x₂=2.

Похожие вопросы